Impact of Silicon Carbide Particles Weight Percentage on the Microstructure, Mechanical Behaviour, and Fractography of Al2014 Alloy Composites - H. S. Vasanth Kumar; K. Revanna; Nithin Kumar; N. Sathyanarayana; N. Madeva; G. A. Manjunath; H. Adisu (Advances in Materials Science and Engineering)
The microstructure, mechanical characteristics, and tensile fractography of Al2014 alloy reinforced composites with 5 and 10% wt. % of 150 to 160 micron-sized SiC particles were investigated in this study. The melt stir process was used to make composites comprising 5 and 10% SiC particles in the Al2014 alloy. To increase the wettability between Al matrix SiC particles, SiC particles were warmed to 300 degrees Celsius before being disseminated into the Al2014 alloy matrix in two phases. SEM, EDS, and XRD were used to examine the specimens micro-structurally. ASTM standards were used to evaluate the mechanical characteristics of micro SiC particles reinforced Al alloy composites with a content of 5 to 10%. SEM and EDS microstructural tests revealed the existence and dissemination of micro SiC particles in the Al2014 matrix. The addition of 5 and 10% weight % of micro SiC particles to Al2014 alloy improved its hardness, ultimate, yield, and compression strength. With the addition of 10 wt. % of SiC, the hardness, ultimate strength, yield strength, and compression strength of Al2014 alloy improved to 15.96%, 35.2%, 43.8%, and 38.7%, respectively. Furthermore, the presence of SiC particles reduced the ductility of Al2014 alloy. SEM microphotographs were used to examine the manufactured Al2014 with SiC composites for tensile fracture analysis, revealing the various mechanisms intricate in tensile fracture.